Adaptation of SIVmac to baboon primary cells results in complete absence of in vivo baboon infectivity - Obregon-Perko, Veronica; Mannino, Amanda; Ladner, Jason T.; Hodara, Vida; Ebrahimi, Diako; Parodi, Laura; Callery, Jessica; Palacios, Gustavo; Giavedoni, Luis D. (Frontiers in Cellular and Infection Microbiology, 2024)
While simian immunodeficiency virus (SIV) infection is non-pathogenic in naturally infected African nonhuman primate hosts, experimental or accidental infection in rhesus macaques often leads to AIDS.Baboons, widely distributed throughout Africa, do not naturally harbor SIV, and experimental infection of baboons with SIVmac results in transient low-level viral replication. Elucidation of mechanisms of natural immunity in baboons could uncover new targets of antiviral intervention. We tested the hypothesis that an SIVmac adapted to replicate in baboon primary cells will gain the capacity to establish chronic infections in vivo. Here, we generated SIVmac variants in baboon cells through serial passage in PBMC from different donors (SIVbn-PBMC s1), in PBMC from the same donors (SIVbn-PBMC s2), or in isolated CD4 cells from the same donors used for series 2 (SIVbn-CD4). While SIVbn-PBMC s1 and SIVbn-CD4 demonstrated increased replication capacity, SIVbn-PBMC s2 did not.Pharmacological blockade of CCR5 revealed SIVbn-PBMC s1 could more efficiently use available CCR5 than SIVmac, a trait we hypothesize arose to circumvent receptor occupation by chemokines.Sequencing analysis showed that all three viruses accumulated different types of mutations, and that more non-synonymous mutations became fixed in SIVbn-PBMC s1 than SIVbn-PBMC s2 and SIVbn-CD4, supporting the notion of stronger fitness pressure in PBMC from different genetic backgrounds.Testing the individual contribution of several newly fixed SIV mutations suggested that is the additive effect of these mutations in SIVbn-PBMC s1 that contributed to its enhanced fitness, as recombinant single mutant viruses showed no difference in replication capacity over the parental SIVmac239 strain.The replicative capacity of SIVbn-PBMC passage 4 (P4) s1 was tested in vivo by infecting baboons intravenously with SIVbn-PBMC P4 s1 or SIVmac251. While animals infected with SIVmac251 showed the known pattern of transient low-level viremia, animals infected with SIVbn-PBMC P4 s1 had undetectable viremia or viral DNA in lymphoid tissue. These studies suggest that adaptation of SIV to grow in baboon primary cells results in mutations that confer increased replicative capacity in the artificial environment of cell culture but make the virus unable to avoid the restrictive factors generated by a complex multicellular organism.